EFFECT OF OLEA EUROPAEA AFRICANA L. (OLEACEAE) LEAF AQUEOUS EXTRACT ON CASTOR OIL-INDUCED DIARRHOEA IN MICE - Amabeoku, G.; Bamuamba, K. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The leaf aqueous extract of O. europaea ssp. africana L. was tested for antidiarrhoeal activity against castor oil–induced diarrhoea in mice. Acute toxicity studies and phytochemical analysis of O. europaea africana were also carried out. O. europaea ssp. africana significantly reduced the number of diarrhoeal episodes induced by castor oil. O. europaea ssp. africana also significantly decreased the stool mass produced as a result of castor oil-induced diarrhoea and significantly prolonged the onset of the diarrhoea. The number of animals exhibiting diarrhoea over a five hour period was significantly decreased by O. europaea ssp. africana. Similarly, loperamide completely abolished the diarrhoeal episodes and stool mass, and protected the animals against castor oil-induced diarrhoea. The results obtained suggest that the aqueous extract of O. europaea ssp. africana has antidiarrhoeal properties. The relatively high LD50 of 3475 mg/kg (p.o.) obtained with the aqueous extract indicates that the plant species may be safe and/or nontoxic in mice. The phytochemical analysis done on the plant species showed the presence of saponins, tannins, flavonoids, triterpene steroids and reducing sugars.